Positive Allosteric Modulation of Insect Olfactory Receptor Function by ORco Agonists - Tsitoura, Panagiota; Iatrou, Kostas (Frontiers in Cellular Neuroscience, 2016)
Insect olfactory receptors (ORs) are heteromeric ligand-gated cation channels composed of a common olfactory receptor subunit (ORco) and a variable subunit (ORx) of as yet unknown structures and undetermined stoichiometries. In this study, we examined the allosteric modulation exerted on Anopheles gambiae heteromeric ORx/ORco olfactory receptors in vitro by a specific class of ORco agonists (OAs) comprising ORcoRAM2 and VUAA1. High OA concentrations produced stronger functional responses in cells expressing heteromeric receptor channels relative to cells expressing ORco alone. These OA-induced responses of ORx/ORco channels were also notably much stronger than those obtained upon administration of ORx-specific ligands to the same receptors. Most importantly, small concentrations of OAs were found to act as strong potentiators of ORx/ORco function, increasing dramatically both the efficacy and potency of ORx-specific odorants. These results suggest that insect heteromeric ORs are highly dynamic complexes adopting different conformations that change in a concerted fashion as a result of the interplay between the subunits of the oligomeric assemblies, and that allosteric modulation may constitute an important element in the modulation and fining tuning of olfactory reception function.